2020
DOI: 10.1002/jmri.27153
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Based on MRI for Differentiation of Low‐ and High‐Grade in Low‐Stage Renal Cell Carcinoma

Abstract: Background Pretreatment determination of renal cell carcinoma aggressiveness may help to guide clinical decision‐making. Purpose To evaluate the efficacy of residual convolutional neural network using routine MRI in differentiating low‐grade (grade I–II) from high‐grade (grade III–IV) in stage I and II renal cell carcinoma. Study Type Retrospective. Population In all, 376 patients with 430 renal cell carcinoma lesions from 2008–2019 in a multicenter cohort were acquired. The 353 Fuhrman‐graded renal cell carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 36 publications
(69 reference statements)
1
19
0
Order By: Relevance
“…Our study was generally in line with prior reports of renal cancer assessed with machine learning radiomics (29,(38)(39)(40)(41). Our model performance was comparable to the prior studies which had AUC values reaching 0.86~0.98 for predicting pathological grade of renal cancers.…”
Section: Discussionsupporting
confidence: 89%
“…Our study was generally in line with prior reports of renal cancer assessed with machine learning radiomics (29,(38)(39)(40)(41). Our model performance was comparable to the prior studies which had AUC values reaching 0.86~0.98 for predicting pathological grade of renal cancers.…”
Section: Discussionsupporting
confidence: 89%
“…Deep learning models can recognize predictive features directly from images by utilizing a back-propagation algorithm which recalibrates the model's internal parameters after each round of training [10] . Recent studies have shown the potential of deep learning in the assessment of solid liver lesions on ultrasonography [11] , renal lesions [ 12 , 13 ] and glioma on MR Imaging [ 10 , [14] , [15] , [16] , [17] ] and abnormal chest radiographs [18] .…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous efforts have been made to derive the clinical or histological characteristics from radiological images, the majority of these studies solely pertain to a single task, either target segmentation or image classification [10,[29][30][31][32]. A framework that systematically performs cancer segmentation and evaluation is still rare.…”
Section: Discussionmentioning
confidence: 99%